PENGARUH KEWIBAWAAN GURU PAI TERHADAP MOTIVASI BELAJAR SISWA SMK AL KAUTSAR - Usman Sutisna (Faktor Jurnal Ilmiah Kependidikan, 2016)
Abstract: This study aims to determine the influence of significant between PAI teacher authority on students motivation. This study uses a quantitative approach with motede (Field Research) descriptive correlational. Samples taken as many as 60 people purposive sampling, the sampling is based on a class that will be used as the respondent. Classes are referred to in this research is class X SMK from all departments at SMK Al Kawthar South Jakarta. The result is calculated through analysis of statistical data using the percentage then calculate the correlation by using Product Moment Correlation formula. From the calculation through the formula product moment correlation r values '3f '3fobtained arithmetic done by 0.58, while in the t table at significance level of 5% was obtained 0.254 numbers and at significant level of 1% was obtained 0.330 figure. It can be concluded that there is a significant correlationbetween PAI teacher authority on students' motivation accepted or approved.Keyword : PAI Teacher Authority, Students Learning Motivation